USING FACEBOOK TO PRACTICE WRITING SKILL: WHAT DO THE STUDENTS THINK? - Nikenda Putri; Dyah Aminatun (fsip.teknokrat.ac.id, 2021)
The research aims to find out students’ perceptions toward using Facebook to practice their writing skill. The sample of this study consisted of 20 participants of English major students. The main instrument used in this research was questionnaire which consisted of two sections. The first section was about the students’ general performance on Facebook and its influences. The second was about the influence of Facebook on students’ writing skill. The semi-structured interview was also conducted to support the validity of the data. The result shows that students think that by using Facebook, students can practice their writing by creating English caption and also writing comment on English fan page. Besides that, students can also improve their vocabulary by reading to the captions on the Facebook. Students also can have more idea to write by reading the topic discussed in this social media. It can be concluded that students give positive thought of using Facebook to practice their writing skill.